Boosting the L2 Learners’ Reading Comprehension Capability by Employing Nearpod Media - Amy Mastura; Silvi Listia Dewi; Misnar Misnar; Intan Zuhra; Misnawati Misnawati (IJORER : International Journal of Recent Educational Research, 2023)
Objective: This study aimed to enhance L2 learners' reading comprehension by integrating Nearpod media into the teaching strategy at Universitas Almuslim. The main goal was to evaluate the effectiveness of this technology-based learning in boosting L2 reading comprehension. Method: A pre-experimental research design was employed in this study, in which the L2 learners at Universitas Almuslim were grouped without a control group for comparison. Pre-tests and post-tests were conducted using the Nearpod platform to assess the L2 learners' reading comprehension skills. The data acquired from the pre-test and post-test were quantitatively analyzed with SPSS Statistics Output to determine whether or not there was a significant difference when using the Nearpod media in class. Results: The outcomes revealed a significant difference in the L2 reading comprehension when exposed to Nearpod. It showed that the post-test reading comprehension mean score was higher than the pre-test mean score. Thus, the null hypothesis (Ho) was rejected, whereas the alternative hypothesis (Ha) was accepted. Novelty: By integrating technology into the classroom, this study contributes to the growing body of knowledge on effective strategies for language learning. The findings emphasize the potential of Nearpod media to engage and empower L2 learners, providing a novel and prospective option for boosting language teaching, particularly in reading comprehension.